Intracranial Subdural Hematoma after Spinal Anesthesia: Report of Two Cases with different Outcomes - Guilherme Gago; Otávio Garcia Martins; Pedro Luís Gobatto; Fernando Antônio de Oliveira Costa; Ricardo Santin; Matheus Prado Magalhães; Antônio Delacy Martini Vial (Brazilian Neurosurgery, 2019)
Spinal anesthesia is a technique commonly used for local anesthesia and in obstetric surgeries. Rarely, the formation of an intracranial subdural hematoma (SDH) may result from spinal anesthesia, constituting a serious condition that often leads to severe neurological deficits. The presentation and course of this pathology may occur in a completely different way, which makes its diagnosis and management difficult. In the present article, the authors report two cases of patients with intracranial SDH after spinal anesthesia with completely different presentations and outcomes, demonstrating the variability of the manifestations of this condition. A quick review of key points of its pathophysiology, symptomatology, diagnosis, and treatment was also performed.